Perceived Risk of HIV Infection and Associated Factors among Secondary School Students in Wakiso District, Uganda - Charles Peter Osingada; Caroline Nabasirye; Sara Groves; Tom Denis Ngabirano (Hindawi Limited, 2016)
Introduction. HIV/AIDS remain a major public health problem in Uganda and 4% of individuals aged between 15 and 24 years are living with HIV. Few studies have examined HIV risk perception among adolescents in Uganda. Methods. We conducted a cross-sectional study among 379 secondary school students using multistage sampling techniques. Data were collected using an interviewer-administered questionnaire. Descriptive and logistic regression analyses were conducted. Results. One hundred ninety-one (49.6%) of the respondents perceived themselves to be at risk of contracting HIV, 174 (45.9%) had ever had sex, and 139 (80.4%) had first sexual encounter at 16 years or less. Only 49% of respondents who had sex within 12 months used a condom. Being older than 17 years, knowing someone who died of HIV, early sexual debut, and having ever had sex were associated with perceived risk of contracting HIV. After multivariate analysis, knowledge of someone who died of HIV (Adjusted Odds Ratio (AOR) 16, 95% CI 1.49-171.97) remained statistically significant. Conclusion. Many secondary school students perceived themselves to be at risk of contracting HIV; this perception is associated with knowing someone who died of HIV/AIDS. There is a need to strengthen HIV risk reduction interventions in Wakiso secondary schools.